Pengembangan Lembar Kegiatan Siswa (LKS) Berbasis Gambar Pada Materi Sistem Pencernaan Untuk SMP Kelas VIII Semester 1 - rahmi, Dahlia; Indriati, Gustina; Fadilah, Muhyiatul (Pendidikan Biologi, 2013)
Student work sheets are sheets which contains tasks that must be done by learners. Tasks instructed in sheet activities must have clear basic competencies to achieved, and allows teachers to direct student in learning. Based on observations and interviews that have been conducted in SMPN 1 Palembayan, teaching material in the form of worksheets on the digestive system have been used in learning, but it less attractive in color and is to yet equipped contextual images. The aim of this study, work produces students works sheet images based on the digestive system material and know its validaty and practicality. This research used 4-D models with three steps are define, design, develop. and disseminateÂ  phase is not performed in this study. Type of data is the primary data obtained directly from lecturers, teachers and students through a questionnaire validity and practicality. Analysis of the data used descriptive analysis. Student works sheets Research results this worksheet has validity in form that criteria valid (84,87%), and the practicality criteria are very practical by on teacher (90,83%) while practical criteria (83,63%) by student it can be concluded that student worksheet produced stated valid and practice.Â